“Bringin’ Sexy Back” (and With it, Women): Shusterman Beyond Foucault on the Greeks - Matthew Sharpe (Eidos. A Journal for Philosophy of Culture, 2022)
Preview: /Commentary: Richard Shusterman, Ars Erotica: Sex and Somaesthetics in the Classical Arts of Love (Cambridge: Cambridge University Press, 2021), 436 pages./ Like other contributors, I would like to begin by expressing my respect and admiration for the scale and scope of Richard Shusterman’s achievement in Ars Erotica. The Preface acknowledges “the vast amount of material” involved in this project of charting “the history of erotic theory in the world’s most influential premodern cultures,” with each chapter on a different cultural tradition potentially meriting its own monograph (AE, x, xi). As a scholar who has worked in depth on the work of Pierre Hadot, as well as Michel Foucault’s works on the practices of philosophy conceived as an art or craft (technê) of living in the Western tradition, my response will necessarily be more limited. It will address in detail just the first major chapter of the book – especially as I note with appreciation the piece in this symposium by Marta Faustino on the relations between the ars vivendi and ars erotica. I take some comfort in accepting these limitations from the statement of a particular debt that Shusterman proffers in his Preface to Foucault’s works in the finally-not-completed History of Sexuality series. The author notes both what he owes to Foucault on sexuality, particularly in his studies on the ancient Greeks and Romans, as well as his differences from Foucault’s work.